2017
DOI: 10.1002/2016gb005489
|View full text |Cite
|
Sign up to set email alerts
|

Untangling biogeochemical processes from the impact of ocean circulation: First insight on the Mediterranean dissolved barium dynamics

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 59 publications
3
10
0
Order By: Relevance
“…High particulate iron and aluminum concentrations were also observed at these stations Menzel et al, 2017Menzel et al, , 2018. Enrichment in 226 Ra has indeed been observed in hydrothermal system plumes at mid-ocean ridge (Kadko, 1996;Kadko and Moore, 1988;Kipp et al, 2017;Rudnicki and Elderfield, 1992). Moreover, the 226 Ra enrichments are accompanied by slight Ba enrichments, which may support the hydrothermal origin hypothesis, since hydrothermal venting at mid-ocean Ridge constitutes the second major external source of Ba to the ocean (Edmond et al, 1979).…”
Section: Ra Inputs and Their Relationship With Bamentioning
confidence: 54%
“…High particulate iron and aluminum concentrations were also observed at these stations Menzel et al, 2017Menzel et al, , 2018. Enrichment in 226 Ra has indeed been observed in hydrothermal system plumes at mid-ocean ridge (Kadko, 1996;Kadko and Moore, 1988;Kipp et al, 2017;Rudnicki and Elderfield, 1992). Moreover, the 226 Ra enrichments are accompanied by slight Ba enrichments, which may support the hydrothermal origin hypothesis, since hydrothermal venting at mid-ocean Ridge constitutes the second major external source of Ba to the ocean (Edmond et al, 1979).…”
Section: Ra Inputs and Their Relationship With Bamentioning
confidence: 54%
“…There is a strong positive correlation between dissolved barium (Ba d ) and silicic acid throughout the global ocean, and a similar trend between Ba d and alkalinity (e.g. Hoppema et al, 2010;Jacquet et al, 2005;Jacquet et al, 2007;Jacquet et al, 2008;Jeandel et al, 1996;Jullion et al, 2017;Thomas et al, 2011), likely a result of relatively deep release of Ba during particulate organic matter remineralization, coupled with large scale ocean circulation (Bates et al, 2017;Horner et al, 2015;Jeandel et al, 1996;Lea, 1993). Water column, sediment trap, and core top studies have also revealed a relationship between excess barium in the particulate phase ( total barium corrected for lithogenic input, Ba xs ) and particulate organic carbon (POC) .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Jullion et al (2017) -by using a parametric OMP analyses as applied in the Mediterranean Sea -also reported quantification of the nonconservative component of the Ba signal and suggested that the Ba negative anomalies potentially reflected Ba subtraction during barite formation occurring during POC remineralization. The winter deep convection in the Labrador Sea may also potentially explain these relatively deep Ba anomalies by transporting negative Ba and 226 Ra anomalies waters toward the deep sea, as was observed in the Mediterranean Sea (Jullion et al, 2017). With the exception of the acantharian skeletons that may impact the dissolved 226 Ra / Ba ratios in the upper 200 m, the removal of 226 Ra and Ba that takes place deeper in the water column or that involves other processes (e.g., barite precipitation) does not seem to significantly affect the dissolved 226 Ra / Ba ratios.…”
Section: High Particulate Excess Ba (Bamentioning
confidence: 90%